Relationship between periodontal disease and carotid atheromatous plaque: A clinico-ultrasound study - Surekha Ramrao Rathod; Farooque Khan; Trupti Satish Sarda; Anubha Raj (Wolters Kluwer Medknow Publications, 2015)
Aim: The aim of this study was to determine the relationship between Carotid atheromatous plaque in carotid artery with periodontal health and disease clinically and ultrasonographically and secondarily whether these relations are dependent on the level of serum high-density lipoprotein (HDL) cholesterol. Materials and Methods : The cross-sectional study was carried out on 60 subjects. Of which 30 subjects with chronic periodontitis and 30 subjects with healthy periodontium were recruited and they underwent ultrasound scanning of common carotid arteries to determine carotid plaque thickness. Clinical parameters measured were probing pocket depth, clinical attachment loss, plaque index, gingival index and biochemical parameters included total cholesterol, triglycerides, and HDL levels. Results : Periodontal disease is positively associated with carotid atherosclerosis. Plaque thickness and prevalence of carotid atheromatous plaque were significantly higher in the test group as compared to the control group. In the test group the mean carotid atheromatous plaque thickness was found to be 2.18 mm whereas in the control group it was found to be 0.14 mm. In test group, there was a positive and highly significant correlation of probing depth (PD) with triglycerides and total cholesterol levels and carotid atheromatous plaque thickness but a negative correlation between PD and HDL, triglycerides and total serum cholesterol levels in healthy subjects. HDL was significantly less in test group when compared with a control group with a P = 0.004. Conclusion: An inter-relationship between periodontal disease and the presence of atheromatous plaque exists. The prevalence of both periodontitis and atherosclerosis is very high. Periodontitis should be diagnosed and treated at its earliest and hence that clinician and public health practitioner can control the epidemic of cardiovascular diseases and reduce mortality.